SIFAT FISIK, KIMIA DAN ORGANOLEPTIK PERMEN JELLY TOMAT DENGAN VARIASI JENIS GULA DAN BAHAN PEMBENTUK GEL - Catur Budi Handayani; Sri Hartati; Afriyanti Afriyanti (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2021)
The purpose of this study was to determine the characteristics of the physical, chemical characteristic (reducing sugar content) and organoleptic characteristic (taste, preference) tomato jelly with various types of sugar (glucose, dextrose and sucros and gelling agents (agar and jelly powder) are added. The study used a factorial design. The results showed that the water content of the tomato jelly candy ranged from 7.4 to 10.03% and there was no significant difference between all treatments. The reducing sugar content ranged from 0.59 to 3.46% and there was a significant difference between candy using dextrose and other types of sugar. The organoleptic characteristic of taste showed that the most preferred tomato jelly candy was candy made using sucrose and agar with a score of 3.03 (delicious) and the least preferred was jelly candy with dextrose agar. The overall organoleptic test of liking showed that the most preferred candy was candy made with glucose agar and the least preferred candy was candy made using dextrose agar. Keywords: agar, jelly powder, tomato jelly candy, sugar